Strategic Approaches in Corporate Financial Management in Response to Economic Uncertainty - Andiana, Baiq Dewi Lita (CV. HEI PUBLISHING INDONESIA, 2025)
Economic policy uncertainty arising from fiscal, monetary, and regulatory fluctuations poses significant challenges to corporate financial decision-making. Financial managers are therefore required to maintain business stability and sustainability amid dynamic and unpredictable conditions. This study examined financial management strategies adopted by companies in response to economic policy uncertainty and analyzed their theoretical and practical implications. Using a descriptive qualitative approach through a literature review, data were collected from scientific journals, academic books, and reports published by international financial institutions. The findings reveal that companies tend to implement conservative and flexible strategies, including increasing cash reserves, reducing leverage, diversifying business and operational activities, and utilizing financial derivatives for risk mitigation. Firms also tend to delay large-scale investments and rely more heavily on internal financing. These responses reflect corporate efforts to cope with heightened policy risk and support the relevance of trade-off theory, pecking order theory, and signaling theory in corporate financial decision-making under uncertainty. Overall, adaptive and risk-anticipative financial management strategies have become crucial for enhancing corporate resilience and flexibility. This study contributes both conceptually and practically to the development of stronger corporate financial policies in the face of global and domestic economic uncertainty